Artocarpus heterophyllus Lam (jackfruit) processing equipment: Research insights and perspectives. (2nd December 2021) - Nelluri, Puja; Venkatesh, Thulasiraman; Kothakota, Anjineyulu; Pandiselvam, Ravi; Garg, Ramandeep; Mousavi Khaneghah, Amin
Abstract: India is the largest producer of jackfruit ( Artocarpus Heterophyllus Lam .) all over the world. It is an underutilized seasonal fruit rich in vitamins, minerals, proteins, and carbohydrates. A significant chunk of the jackfruit production is wasted due to a lack of postharvest technological interventions. Due to its bulky nature, thickness, and spiky skin, operations like peeling, cutting, and coring are difficult to perform manually. Recently, there is a considerable improvement in the mechanization of jackfruit postharvest processing, which helps to reduce the wastage by 80% in its production and utilization. This review summarizes the recently developed varied types of machinery, procedures, and working mechanism of various postharvest operations such as peeling, cutting, coring, bulb removal, and seed processing. Moreover, it critically evaluates and compares the machinery for each stage of unit operation involved in jackfruit processing. The development of various thermal processing techniques such as blanching, canning, boiling, and drying is also discussed in detail. However, on comparing thermal processing with other processing aids, there is always a critical nutrients loss during thermal processing. This review also finally explores the jackfruit potential for industrial application and commercialization. Practical Applications: Unit operations involving preprocessing of jackfruits such as peeling, cutting, coring, bulb removal, seed roasting, and seed dehulling remain the most tedious operation in jackfruit processing due to its irregular shape and hard surface. Manual operation of such unit operations consumes much time and causes drudgery. Hence, the development of suitable equipment for such unit operations becomes inevitable and helps make the jackfruit processing faster and more efficient. Critical analysis of various machineries for jackfruit processing will be of great use for industries to learn about various machineries used in jackfruit processing. Abstract : Jack fruit various parts, processing methods equipment : Research Insights and Perspectives